2000
DOI: 10.1359/jbmr.2000.15.10.1912
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule 1 Discriminates Functionally Different Populations of Human Osteoblasts: Characteristic Involvement of Cell Cycle Regulators

Abstract: The concept of differential regulation of certain adhesion molecules on different cell subsets and their relevance to cell functions has emerged in recent years. The initial event in bone remodeling is an increase in osteoclastic bone resorption and cell adhesion between osteoclastic precursors and bone marrow stromal cells or osteoblasts is known to commit the osteoclast development. Here, we show that human osteoblasts can be divided into two subsets based on the expression of the intercellular adhesion mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 44 publications
4
67
2
Order By: Relevance
“…Possibly, cultured osteoblasts are heterogeneous in their expression of cell adhesion molecules. Such heterogeneity has previously been described for osteoblasts expressing ICAM-1, where ICAM-1-positive osteoblasts were particularly involved in the attachment and subsequent differentiation of osteoclast precursor cells (26). Interestingly, we found that AZD0530 caused an arrest at the prefusion stage of osteoclast precursor cells (i.e., they did attach to osteoblasts).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Possibly, cultured osteoblasts are heterogeneous in their expression of cell adhesion molecules. Such heterogeneity has previously been described for osteoblasts expressing ICAM-1, where ICAM-1-positive osteoblasts were particularly involved in the attachment and subsequent differentiation of osteoclast precursor cells (26). Interestingly, we found that AZD0530 caused an arrest at the prefusion stage of osteoclast precursor cells (i.e., they did attach to osteoblasts).…”
Section: Discussionsupporting
confidence: 77%
“…5 Considering the effect of AZD0530 on the sequence of events in osteoclast formation, it became apparent that AZD0530 did not interfere with the initial binding of PBMCs to osteoblasts, but did so with stages of osteoclast differentiation. In line with the lack of an effect on binding is the unaltered mRNA expression of ICAM-1, a cell-cell adhesion molecule important in osteoclastogenesis (26). An intriguing finding was the difference in binding of PBMCs to osteoblasts.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Mutinuclear osteoclast-like cell formation from osteoblasts is related to the upregulation of p21, with the majority of cells remaining at the G0/G1 phase (Tanaka et al, 2000). The integrity of p21 within centrosomes is related to apoptosis, multinucleation and normal mitotic progression .…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that although SC express early osteogenic markers, their differentiation to a classic fully osteoblastic phenotype cannot be achieved even after appropriate induction. To verify if SC might be considered similar to another cell type, the socalled ''bone lining cell'' [12], expressing very low levels of Type I collagen and osteocalcin and known to contribute to bone collagen degradation, we analyzed the mRNA for ICAM-1, the expression of which is increased in this osteoblast subtype [12,43]. Interestingly, ICAM-1 plays a pivotal role in osteoclastogenesis, because osteoblasts expressing ICAM-1 support bone resorption activity [44,45].…”
Section: Cell Culturesmentioning
confidence: 99%